Relevansi Nilai-Nilai Pendidikan Akhlak Dalam Surah Luqman Ayat 12-19 Terhadap Krisis Moral : Moral Education Values in Surah Luqman Verses 12–19 and Their Relevance to the Moral Crisis Among Adolescents - Afifah Nur Khusna; Rahmania Nur Aslami; Zahrifah Rahmah; Afif Abdus Syakur (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2026)
The moral crisis among adolescents in the digital era has become one of the major concerns in the field of education. The development of technology, social media, and artificial intelligence (AI) has brought both positive and negative impacts on adolescent character formation. Phenomena such as declining politeness, cyberbullying, decreasing respect toward parents and teachers, and the misuse of social media indicate the importance of strengthening moral education based on Qur’anic values. This study aims to analyze the values of moral education contained in Surah Luqman verses 12–19 and their relevance to the moral crisis among adolescents in the digital era. This research employed a qualitative method using a library research approach. The primary data sources consisted of Surah Luqman verses 12–19 and Tafsir Al-Misbah, while secondary data were obtained from journals, books, and previous studies related to the topic. Data were collected through documentation techniques and analyzed using content analysis. The findings reveal that Surah Luqman verses 12–19 contain values of monotheistic education, devotion to parents, worship education, amar ma’ruf nahi munkar, patience, and the prohibition of arrogance. These values are highly relevant to adolescent character building in the digital era, as they can serve as guidelines for developing religiosity, self-control, communication ethics, and social awareness. Therefore, moral education in Surah Luqman verses 12–19 can be considered as one of the solutions to overcome the moral crisis among adolescents in the modern era.